CORRELATION OF PROSTATE CANCER WITH DISEASES OF THE CARDIOVASCULAR SYSTEM AND TYPE 2 DIABETES - Tillyashaikhov Mirzagolib Nigmatovich; Boyko Yelena Vladimirovna; Alimov Jaloliddin Usmonkhon ugli (Web of Journals Publishing, 2024)
This study examines the potential correlation between prostate cancer and two prevalent conditions: cardiovascular disease and type 2 diabetes. Prostate cancer is a significant global health issue, and comprehending its association with other common diseases is crucial for comprehensive patient care and public health initiatives. The study investigates the correlation between prostate cancer and cardiovascular diseases, including hypertension and atherosclerosis, as well as the correlation between prostate cancer and type 2 diabetes mellitus. The results provide insight into potential shared risk factors, underlying mechanisms, and implications for diagnosis, treatment, and prevention strategies for these diseases. This abstract summarises key aspects of the study, highlighting its importance in furthering the understanding of the complex relationships between prostate cancer and cardiovascular disease as well as type 2 diabetes.
Keywords: prostate cancer, cardiovascular diseases, type 2 diabetes mellitus.